Model Financial Satisfaction Berbasis Financial Literacy dan Self-Control Melalui Financial Well-Being pada Karyawan Perempuan Bank BUMN di Kota Jambi - Dea Rusita; Besse Wediawati; Andang Fazri; RTS Ratnawati (Keizai, 2025)
Financial satisfaction is an important indicator of individual financial well-being, especially for female employees who often face the dual burden of managing work and household finances. This study aims to analyze the influence of financial literacy and self-control on financial satisfaction through financial well-being as a mediating variable among female employees of state-owned banks in Jambi City. This quantitative research uses a survey method with 100 respondents selected through purposive sampling. Data analysis uses Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. The results show that: financial literacy has a positive and significant effect on financial satisfaction; self-control has no direct effect on financial satisfaction; both financial literacy and self-control have a positive and significant effect on financial well-being; financial well-being has a strong positive effect on financial satisfaction; and financial well-being significantly mediates the relationship between financial literacy and self-control on financial satisfaction. This study provides important implications for financial education programs and employee welfare policies in the banking sector.